Boricua Energy Justice Visualization - Willian A. Pacheco-Cano; Carlos A. Peña-Becerra; Marcel Castro-Sitiriche (Energies)
The impact of natural hazards on the Puerto Rican electric system significantly affects the well-being of its population, particularly affecting populations in remote areas. The present study aims to identify the most affected geographic regions using a complementary approach that leverages open source governmental data. By harnessing the power of comprehensive data and utilizing a graphical analysis tool—a set of open access dashboards with maps and graphs—positive change can be fostered, providing stakeholders with comprehensive data for informed decision-making. The dashboards facilitate the identification, association, and analysis of different metrics such as customers without services, SAIDI (System Average Interruption Duration Index), SAIFI (System Average Interruption Frequency Index), and CHoLES (Customers Hours of Lost Electric Service). Additionally, the dashboard provides information on the progress of the net metering, demonstrating the rapid integration of PV (photovoltaic) and BES (battery energy storage) systems. Interactive dashboards for stakeholders to analyze key metrics such as SAIDI, SAIFI and CHoLES were designed and built using an interactive data visualization platform.